Interrogating the Socio-Cultural Experiences of the Urhobo People in the Urhobo Disco Music and the Role of the Radio Media - Okpeki, Philo Igue (Pedagogika Społeczna Nova, 2021)
Often times, music has been seen as an art form which embodies and boasts a lot of rich socio-cultural experiences and expressions. More so, is the Urhobo music which embodies so many cultural values that are impalpable yet so much cherished. It is observed that the traditional music of the Urhobo, which includes the Urhobo Disco music by Okpan Arhibo, is used in various socio-cultural contexts such as burials, in-law greetings, marriages, birthday and naming ceremonies, amongst others.It is the concern of this paper, therefore, to investigate the effectiveness of the role of the radio in broadcasting music, particularly of the Urhobo of Delta State, Nigeria, as a way of promoting the socio-cultural ex- periences of the Urhobo nationality. The paper adopts both the phenomenological and cultural schema theories. The descriptive survey research design is also employed to enable the collection of data from the Management of JFM Radio (95.1fm) and Melody FM (88.6fm), as well as twenty-six participants that were engaged in interview sessions, using a Self-responded Interview Questionnaire of ten vali- dated items involving the Likert moderated type rating scale of four points. Generated data were sub- jected to simple statistics of the mean and standard deviation. Findings show that the compendium of Urhobo music by radio stations enables the spread of the cultural and social experience of the Urhobo people beyond their region. The paper concludes that radio broadcast of traditional music ensures that the cultural experience of the Urhobo is sustained. Hence, the paper recommended that radio stations should give sufficient airtime for the broadcast of Urhobo Disco music. This will allow for the spread of the Urhobo experience in Delta State, Nigeria.